FPGA Implementation of Temperature Controller for PCR Based on Microfluidic Chip - Huang, Yourui; Wang, Jing; Qu, Liguo (Journal of networks, 2014)
In order to meet the requirements such as high precision, small overshoot, fast response in Polymerase Chain Reaction (PCR) when control temperature, this paper designs a PCR microfluidic chip based on temperature control using genetic algorithm PID. The chip adopts genetic algorithm PID to control AT89C51 chip to generate PWM waves which have different duty ratio in order to realize the adjustment and control of temperature. The design of genetic algorithm PID controller is realized by FPGA. In the MATLAB environment, the simulation is conducted using genetic algorithm PID control. The simulation results show that genetic algorithm PID controller which is realized by FPGA can well track the input signal, and the control effect is better.